1998
DOI: 10.1063/1.121580
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative recombination at GaAs homointerfaces fabricated using an As cap deposition/removal process

Abstract: GaAs homointerfaces have been grown by molecular beam epitaxy using the steps of GaAs growth, As cap deposition, wafer storage, thermal desorption of the As cap, and GaAs overgrowth. As cap layers with a thickness of up to 7.8 μm were deposited and the wafers were stored for 3–7 days in ultrahigh vacuum (UHV) or under atmospheric conditions. Nonradiative recombination originating from the GaAs homointerface of wafers stored in UHV could not be detected (interface recombination velocity S≪1000 cm/s), however, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The substrate temperature variations would affect the sticking coefficients of the As at lower temperatures. Studies have shown that the sticking coefficient is nearly exponential with temperature at these low temperatures, 8 so a 10°C variation in substrate temperature could affect the growth rates. Also, the Ascracking cell showed some instability in the As flux during growth.…”
Section: B Growth and Fabrication Of The Dbrmentioning
confidence: 99%
“…The substrate temperature variations would affect the sticking coefficients of the As at lower temperatures. Studies have shown that the sticking coefficient is nearly exponential with temperature at these low temperatures, 8 so a 10°C variation in substrate temperature could affect the growth rates. Also, the Ascracking cell showed some instability in the As flux during growth.…”
Section: B Growth and Fabrication Of The Dbrmentioning
confidence: 99%
“…Subsequent to epitaxial layer growth, the GaAs surface was covered by a protective arsenic cap layer. 10 After loading the wafer into another ultrahigh vacuum chamber, the As cap layer was desorbed and Ga 2 O 3 template growth commenced ͑except when no Ga 2 O 3 template was grown͒ using effusive evaporation of a polycrystalline Ga 2 O 3 source material from a high temperature effusion cell. Ga 2 O 3 template thickness ranges from 0 to 72.8 Å in this study.…”
mentioning
confidence: 99%